2018
DOI: 10.1002/jcp.27219
|View full text |Cite
|
Sign up to set email alerts
|

Peg1/Mest, an imprinted gene, is involved in mammary gland maturation

Abstract: Imprinted genes, which are specific to mammals, play important roles in cell proliferation, differentiation, ontogeny, and other phenomena. Moreover, these genes are considered crucial in the research of mammalian evolution. In the current study, we investigated the association between the expression of paternally imprinted gene paternally expressed 1/mesoderm-specific transcript (Peg1/Mest) and the maturation of the mammary gland. Quantitative real-time polymerase chain reaction analysis of Peg1/Mest gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Igf2, another imprinted gene expressed from the paternal allele, mediates prolactin-induced morphogenesis in the mammary gland (Brisken et al, 2002), and has been shown to be produced specifically by hormone-receptor positive cells in early pregnancy (De Silva, Kunasegaran, Ghosh, & Pietersen, 2015). Recently, it has been reported that paternally expressed Mest is involved in mammary gland maturation; specifically, its expression is increased during gestation contributing to the formation and proliferation of alveoli (Yonekura et al, 2019). The epithelium is not the only site for imprinted gene expression since a study found differential allelic expression of GNAS in human mammary adipose tissue samples (Klenke, Siffert, & Frey, 2011).…”
Section: Evidence For Imprinting In the Mammary Glandmentioning
confidence: 99%
“…Igf2, another imprinted gene expressed from the paternal allele, mediates prolactin-induced morphogenesis in the mammary gland (Brisken et al, 2002), and has been shown to be produced specifically by hormone-receptor positive cells in early pregnancy (De Silva, Kunasegaran, Ghosh, & Pietersen, 2015). Recently, it has been reported that paternally expressed Mest is involved in mammary gland maturation; specifically, its expression is increased during gestation contributing to the formation and proliferation of alveoli (Yonekura et al, 2019). The epithelium is not the only site for imprinted gene expression since a study found differential allelic expression of GNAS in human mammary adipose tissue samples (Klenke, Siffert, & Frey, 2011).…”
Section: Evidence For Imprinting In the Mammary Glandmentioning
confidence: 99%
“…The short isoform of MEST was con rmed in both marsupials and platypus. Since this short isoform associates with mammary gland maturation in mice (Yonekura et al, 2019), it is possible that the evolution of the MEST isoform occurred with the evolution of the mammary gland in the common ancestor of mammals. However, the exact function of the MEST short isoform is currently unknown in any mammal.…”
Section: Discussionmentioning
confidence: 99%
“…Although its exact function is unknown, disruption of MEST imprinting causes developmental defects in placental and fetal growth and abnormal maternal behaviour in mice (Hiramuki et al, 2015;Lefebvre et al, 1998;Mayer et al, 2000). The MEST imprinted isoform also regulates mammary gland maturation in mice (Yonekura et al, 2019). Since the gene is associated with many classical mammal-speci c traits, characterising the evolution of this gene locus across mammals could shed light on how imprinting evolved in the common ancestor of therian mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that imprinting may be crucial in the mammary gland 2 , with some demonstrating functional roles for imprinted genes in this tissue 3,33 . However, although ZFP57 is a major regulator of imprinting, we show that it does not act through imprints in the mammary gland.…”
Section: Discussionmentioning
confidence: 99%